Optical precursors in a weakly dispersive double narrow-resonance dielectric - Jeong, Heejeong; Lee, Chang Won; Dawes, Andrew M.C.; Gauthier, Daniel J. (Optical Society of America, 2019)
We investigate optical precursors transmitted through a double-Lorentz dielectric consisting of two adjacent narrow resonances. Compared to the patterns in a single-Lorentz dielectric, the transmitted envelope shows additional modulation that oscillates at the separation frequency between two resonances, corresponding to the doublet frequency separation. We use the weakly dispersive, narrow-resonance condition to analyze it, which compares favorably to our observations. This work will be meaningful to identify dielectric properties by analyzing multi-resonant media for application of optical communication. © 2019 Optical Society of America